Efektivitas Konsumsi Telur dan Pijat Bayi terhadap Tumbuh Kembang Bayi dalam Pencegahan Stunting: Combining Nutrition and Care: The Impact of Egg Consumption and Infant Massage on Growth and Development for Stunting Prevention - Armina Armina; Aisah Aisah; Yuliana Yuliana; Tina Yuli Fatmawati (Universitas Airlangga, 2026)
Background: Stunting is a chronic nutritional deficiency that affects physical growth, cognitive development, and children’s future independence. Prevention is most effective during the first two years of life, when most brain development occurs. A preliminary study in the working area of Putri Ayu Public Health Center (February 2024) identified 20 children with stunting. Weight loss was also observed in infants over six months due to adaptation from exclusive breastfeeding to complementary foods, although age-appropriate weight gain is expected. While the health center provides supplementary feeding, infant massage has not been utilized as an intervention to support weight gain and developmental stimulation. Infant massage may increase appetite, weight, and developmental progress, and egg consumption is known to improve weight and length in children. Objectives: To determine the effectiveness of infant massage combined with egg consumption on the growth and development of infants aged 6–12 months in preventing stunting. Methods: This quasi-experimental study involved 30 infants aged 6–12 months, divided into 15 infants in the intervention group and 15 in the control group. The intervention group received infant massage and one egg daily, while the control group received one daily egg. Growth and development were measured at baseline and after four weeks. Results: Paired t-tests showed significant differences (p-value<0.05) in weight and length before and after intervention in both groups. Wilcoxon tests indicated significant developmental improvement in the intervention group (p-value=0.004) and the control group (p-value=0.046). Conclusions: Infant massage combined with daily egg consumption is effective in improving growth and development among infants aged 6–12 months.